A rapid-response fluorescent probe for the sensitive and selective detection of human albumin in plasma and cell culture supernatants. Issue 36 (14th March 2016) - Wang, Yi-Ru; Feng, Lei; Xu, Liang; Li, Yan; Wang, Dan-Dan; Hou, Jie; Zhou, Kun; Jin, Qiang; Ge, Guang-Bo; Cui, Jing-Nan; Yang, Ling
Abstract : A rapid-response fluorescent probeACDM was developed for selective and sensitive detection of human albumin (HA) via binding on a non-drug binding site. Abstract : A rapid-response fluorescent probeACDM was developed for the selective and sensitive detection of human albumin (HA) via binding onto a non-drug binding site.ACDM was successfully used to detect trace HA in various biological samples including diluted plasma and cell culture supernatants.